A prospective study of management of tibial plateau fractures by locking compression plate in adults - Gawali, Satish R.; Nair, Pradeepkumar S.; Sonkawade, Venktesh D. (International Journal of Research in Orthopaedics, 2021)
Background: Tibial plateau fractures are one of the most complex and disabling fractures of the knee. The tibial plateau is important in transmitting load through the knee. These fractures need a meticulous management protocol in order to minimize patient's disability in range of movement, stability and reducing the risk of documented complications. The aim of the present study is to study the outcome of tibial plateau fractures managed with a locked compression plate. Methods: This study was conducted at a tertiary-care medical college and hospital, Aurangabad specializing in post-graduate training, where all patients who underwent surgical treatment between September 2018 and October 2020 were included. Patients were assessed using the knee society score (KSS). These evaluations were done at 1, 3, 6, 9 and 12 months. Results: In our study we included 55 patients out of which we found union in 98% of patients with 83% of patients showing good flexion at knee joint (>110 degrees). 85% patients achieved union within 6 months. An excellent KSS grade was seen in 38.2% patients with another 43.6% showing good outcome. 4 patients showed infection and 1 showed non-union. A single case of malunion was seen in our study. Conclusions: Locked compression plates in tibial plateau fractures has revolutionized the way these fractures are managed. Anatomic reduction is of utmost importance. Early physiotherapy which plays key role in preventing knee stiffness, use of bone grafts and good fixation are important for successful outcome.